A retrospective description of primary immunodeficiency diseases at Red Cross War Memorial Children's Hospital, Cape Town, South Africa, 1975-2017 - Moodley, Sashmi (Department of Paediatrics and Child Health, 2024)
Background: Even in the absence of global threat, children with disabilities were underrepresented in monitoring efforts and were less likely to have been included in response strategies during the COVID - 19 pandemic. The harmful effects of the pandemic were expected to be most damaging for those in the poorest countries. Objectives: Our study aimed to report the impact of the COVID-19 pandemic on families of children with disabling conditions in South Africa. Methods: Parents from an online parent network, initiated by Shonaquip Social Enterprise during the pandemic, were invited to participate in an online survey in October 2021. A quantitative analysis was conducted using Stata Statistical Software. Results: Sixty-eight (17%) of 400 parents in the network, completed the survey, 89% were mothers. Children aged 5-12 years represented 43% of the group. Eleven parents (16%) reported child health worsening compared to before the pandemic. Parent concerns included practicalities of infection control measures for their children and concerns about caregivers falling ill. Six (9%) children contracted COVID-19 infection and two (3%) children demised. Few families received telephonic contact from health providers. Indirect effects of the pandemic included loss of income and food shortages in more than half of the families. Twentytwo( 32%) families had opted not to send their children back to school even by the third wave of infections. Some positive experiences of lockdown reported by parents included more family time and the opportunity to reach out to other families, however 33 (49%) parents reported being highly stressed, with five (7%) revealing a need for substances to cope. Most parents (n = 50, 74%) reported feeling that care for children with disabilities was not prioritized in South Africa. Conclusion: This is one of the few studies in South Africa that explored childhood disability during the pandemic. A proportion of caregivers reported deterioration in their children's health during a time of limited access to health services. They have reported loss of family income, reduced access to educational services and challenges to mental health of caregivers. Families did not feel supported. Including the voices of parents highlight a range of challenges that need greater awareness. Post-pandemic, much change in practice is needed for families and children with disabilities.